A case of Wolff–Parkinson–White syndrome in which two-dimensional speckle-tracking echocardiography was useful for identifying the location of the accessory atrioventricular pathway. Issue 3 (4th March 2021) - Tanabe, Junya; Watanabe, Nobuhide; Yamaguchi, Kazuto; Tanabe, Kazuaki
Abstract: Background: In Wolff–Parkinson–White (WPW) syndrome, accessory atrioventricular pathways (AP) result in abnormal pre-excitation around the atrioventricular annuli and produce a dyssynchronous contraction of cardiac chambers. Identification of the AP affects the outcome of catheter ablation. Case summary: We report a case of WPW syndrome and paroxysmal atrial fibrillation in a 65-year-old man. Wolff–Parkinson–White syndrome Type B was suspected from lead V1, but when two-dimensional speckle-tracking echocardiography (2D-STE) was performed, a decrease in regional strain was observed in the anterior basal wall of the left ventricle. We identified the earliest site of atrioventricular conduction, and improvement in the regional strain at the site of ablation was observed after successful AP ablation. Discussion: Various echocardiographic techniques have been investigated as non-invasive alternatives for AP localization. Longitudinal 2D-STE accurately identified contractile abnormalities associated with the AP, allowing us to non-invasively estimate the localization of the AP in WPW syndrome.